2014
DOI: 10.1097/jom.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Workers With Shifts in Hearing by Industry

Abstract: Objective The purpose of this study was to compare the prevalence of workers with National Institute for Occupational Safety and Health significant threshold shifts (NSTS), Occupational Safety and Health Administration standard threshold shifts (OSTS), and with OSTS with age correction (OSTS-A), by industry using North American Industry Classification System codes. Methods 2001-2010 worker audiograms were examined. Prevalence and adjusted prevalence ratios for NSTS were estimated by industry. NSTS, OSTS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
6
19
0
Order By: Relevance
“…Among individuals with chronic tinnitus, hearing thresholds were significantly worse in patients in the HIGH-RISK group compared to those in the LOW-RISK group. This finding is in accordance with the literature [ 3 , 4 , 5 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 43 , 44 , 45 , 47 , 48 , 49 , 50 , 51 , 54 , 55 , 56 , 57 , 58 , 68 , 70 , 74 , 88 ]. Our results showed a worse, although not significant, hearing threshold for high frequencies in the left ear compared to the right among individuals in the HIGH-RISK group; no side difference was found in the LOW-RISK group.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Among individuals with chronic tinnitus, hearing thresholds were significantly worse in patients in the HIGH-RISK group compared to those in the LOW-RISK group. This finding is in accordance with the literature [ 3 , 4 , 5 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 43 , 44 , 45 , 47 , 48 , 49 , 50 , 51 , 54 , 55 , 56 , 57 , 58 , 68 , 70 , 74 , 88 ]. Our results showed a worse, although not significant, hearing threshold for high frequencies in the left ear compared to the right among individuals in the HIGH-RISK group; no side difference was found in the LOW-RISK group.…”
Section: Discussionsupporting
confidence: 94%
“…The association between hearing loss, tinnitus and occupation has been previously demonstrated [ 34 , 43 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. The aim of this study was to survey patients with chronic tinnitus with and without a history of long-term work-related noise exposure, comparing demographic variables, tinnitus and hearing loss characteristics and self-administered questionnaire responses for tinnitus, hearing loss and hyperacusis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This sector is not usually associated with a higher risk of hearing loss, and the prevalence has been estimated to be 9–10% overall [Tak and Calvert, ; Masterson et al, ]. However, other research [Masterson, ] has suggested that this sector has a higher prevalence of shifts in hearing. Shifts in hearing can be early indicators of hearing loss and are a measure of the effectiveness of hearing conservation programs [NIOSH, ].…”
Section: Discussionmentioning
confidence: 99%